2016
DOI: 10.1016/j.jvs.2016.06.100
|View full text |Cite
|
Sign up to set email alerts
|

An institutional study of time delays for symptomatic carotid endarterectomy

Abstract: The majority of our cohort falls short of the recommended 2-week interval to perform CEA. Factors contributing to reduced CEA delay were presentation to an emergency department, in-patient investigations, and a stroke center where a vascular surgeon is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
3
7
1
Order By: Relevance
“…Collaboration with the Ophthalmology and Neurology departments to facilitate urgent GP referrals and review of potential candidates for CEA would be crucial in reducing this source of delay. These were consistent with the findings of other international studies of a similar nature …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Collaboration with the Ophthalmology and Neurology departments to facilitate urgent GP referrals and review of potential candidates for CEA would be crucial in reducing this source of delay. These were consistent with the findings of other international studies of a similar nature …”
Section: Discussionsupporting
confidence: 93%
“…These were consistent with the findings of other international studies of a similar nature. [7][8][9][10] The delay in accessing surgery after assessment by the vascular service is of particular concern and amenable to improvement. The factors contributing to this delay can be divided into departmental resources, timing and patient factors.…”
Section: Discussionmentioning
confidence: 99%
“…Three Canadian studies have found that median delay to surgery from symptom onset varies from 25 to 79 days. 2,5,6 Similar trends are observed in Europe with median times to surgery ranging from 53 to 82 days. [7][8][9][10] Furthermore, studies have found that inpatients undergo carotid endarterectomy (CEA) more quickly with 54% receiving CEA within two weeks vs 20% compared to outpatients.…”
Section: How Does This Improve Population Health?supporting
confidence: 66%
“…[7][8][9][10] Furthermore, studies have found that inpatients undergo carotid endarterectomy (CEA) more quickly with 54% receiving CEA within two weeks vs 20% compared to outpatients. 6 The longest delay in care in one study was found to occur between symptom onset and vascular referral, which included delays to obtaining imaging given wait times for outpatient studies. 5 In a second study, time to carotid imaging was the major factor determining time to revascularization.…”
Section: How Does This Improve Population Health?mentioning
confidence: 97%
“…11,12,17 Both the current study and that of Jetty and colleagues 11 revealed that delayed patient presentation, diagnosis and referral are significant factors resulting in a delay in definitive care. In both studies, patients with amaurosis fugax were less likely to meet the guideline, and those who presented to the emergency department were the most likely to meet the guideline.…”
Section: Openmentioning
confidence: 53%